Oxygen availability influences the incidence of testicular teratoma in Dnd1Ter/+ mice - Bustamante-Marin, Ximena M.; Capel, Blanche (Frontiers in Genetics, 2023)
Testicular teratomas and teratocarcinomas are the most common testicular germ cell tumors in early childhood and young men, and they are frequently found unilaterally in the left testis. In 129/SvJ mice carrying a heterozygous copy of the potent modifier of tumor incidence Ter, a point mutation in the dead-end homolog 1 gene (Dnd1Ter/+), ~70% of the unilateral teratomas arise in the left testis. We previously showed that in mice, left/right differences in vascular architecture are associated with reduced hemoglobin saturation and increased levels of the hypoxia inducible factor-1 alpha (HIF-1α) in the left compared to the right testis. To test the hypothesis that systemic reduction of oxygen availability in Dnd1Ter/+ mice would lead to an increased incidence of bilateral tumors, we placed pregnant females from 129/SvJ Dnd1Ter/+ intercross matings in a hypobaric chamber for 12-hour intervals. Our results show that in 129/SvJ Dnd1Ter/+ male gonads, the incidence of bilateral teratoma increased from 3.3% to 64% when fetuses were exposed to acute low oxygen conditions for 12-hours between E13.8 and E14.3. The increase in tumor incidence correlated with the maintenance of high expression of pluripotency genes Oct4, Sox2 and Nanog, elevated activity of the Nodal signaling pathway, and suppression of germ cell mitotic arrest. We propose that the combination of heterozygosity for the Ter mutation and hypoxia causes a delay in male germ cell differentiation that promotes teratoma initiation.